Changes in the Operative Corridor in Oblique Lumbar Interbody Fusion Between Preoperative Imaging and Intraoperative Cone-Beam Computed Tomography Using Morphometric Analysis. (1st September 2019) - Zehri, Aqib; Soriano-Baron, Hector Enrique; Hsu, Wesley; Neal, Matthew; Wilson, Jonathan L
Abstract: INTRODUCTION: Oblique lumbar interbody fusion (OLIF) is a minimally-invasive technique that relies on a sufficient corridor anterior to the psoas and posterior to vascular structures.This intraoperative corridor is evaluated on preoperative computed tomography (CT) and/or magnetic resonance (MR) imaging to guide patient selection.Previous cadaveric studies and preoperative MR imaging analysis have examined this corridor to determine corridor variations along right- and left-sided approaches and among patient characteristics.This is the first study that directly evaluates the true intraoperative corridor in the lateral decubitus position based on intraoperative 3D imaging. METHODS: We performed a retrospective evaluation identifying patients > 18 yr old who had undergone an OLIF via a left-sided approach at 2 tertiary care centers from 2016 to 2018. Patients with scoliosis greater than 20 degrees, transitional anatomy, and psoas abnormalities were excluded.We recorded demographics and the intraoperative corridor defined by the distance between the left lateral border of the aorta or iliac vessels and anteromedial border of the psoas from L1-L2 through L4-5 disc spaces.This corridor was measured on supine, preoperative MR axial imaging and subsequent intraoperative 3D cone beam CT acquired in the right lateral decubitus position. RESULTS: A total of 33 patients, 15 of whom were female, were included in this study.The average age was 65.4 and body mass index (BMI) was 31 kg/m 2 .There was a statistically significant increase ( P < .05) in the intraoperative corridor from supine to lateral decubitus positioning at all levels.The greatest increase in corridor size was noted at L1-2 (3.1 cm) and least at L4-5 (2.1 cm).There was no statistically significant difference between age, BMI, or gender in the preoperative versus intraoperative corridor. CONCLUSION: This is the first study to provide objective evidence to support that lateral decubitus positioning increases the intraoperative corridor for anterior to the psoas techniques.This information should increase confidence with an anterior to the psoas approach if there is adequate corridor size on supine preoperative imaging evaluation.